APLIKASI AKAD JU’ALAH DALAM MARKETING VILLA SYARIAH OMIRA PADA SEKOLAH ISALMIC ENTREPRENEURSHIP BOARDING SCHOOL GLOBAL CAHAYA NUBUWAH INSANI PURWAKARTA - Hubur, AA; Ida Busnetty ,; Bahtiar Usman,; Abdul Ghofur,; Irfat Hista Saputra,; Syakif Ahmad, (JURNAL PENGABDIAN MANDIRI, 2024)
Akad (a Contract) in Sharia business transactions is one of the most important instruments. Because the contract is one of the determinants of whether the transaction is in accordance with the rules of sharia or not. A transaction can be said to be valid if the contract made is not in accordance eith its provisions. Ju’alah is one of the contracts that is commonly applied in sharia busines. Ju’alah is a promise or commitment (iltizam) to provide certain rewards for achieving the specified results of a job. This counseling aims to make the students of the entrepreneur school of the Global Cahaya Nubuwwah Insani Purwakarta Foundation able to understand and apply the ju’alah contract when marketing villa shatia Omira which is one of the business sectors by the Global Cahaya Nubuwwah Insani Purwakarta.